When Legends Fall Silent Our Ways Are Lost: Some Dimensions of the Study of Aging among Native Canadians - Vanderburgh, Rosamond M. (Culture, 1982)
This discussion of some of the dimensions of the study of aging among Native Canadians leans heavily upon Holzberg (1981). I refer to two dimensions that she has identified (lack of homogeneity in ethnic categories and the situational environment) and indicate how these are relevant in regard to Native people. I discuss urbanization as a third dimension, and present an ethnographic example that can be related to all three dimensions. This example is also shown to be relevant to the modernization theory of aging.